The trauma registry compared to All Patient Refined Diagnosis Groups (APR-DRG). Issue 5 (May 2017) - Hackworth, Jodi; Askegard-Giesmann, Johanna; Rouse, Thomas; Benneyworth, Brian
Abstract: Background: Literature has shown there are significant differences between administrative databases and clinical registry data. Our objective was to compare the identification of trauma patients using All Patient Refined Diagnosis Related Groups (APR-DRG) as compared to the Trauma Registry and estimate the effects of those discrepancies on utilization. Methods: Admitted pediatric patients from 1/2012–12/2013 were abstracted from the trauma registry. The patients were linked to corresponding administrative data using the Pediatric Health Information System database at a single children's hospital. APR-DRGs referencing trauma were used to identify trauma patients. We compared variables related to utilization and diagnosis to determine the level of agreement between the two datasets. Results: There were 1942 trauma registry patients and 980 administrative records identified with trauma-specific APR-DRG during the study period. Forty-two percent (816/1942) of registry records had an associated trauma-specific APR-DRG; 69% of registry patients requiring ICU care had trauma APR-DRGs; 73% of registry patients with head injuries had trauma APR-DRGs. Only 21% of registry patients requiring surgical management had associated trauma APR-DRGs, and 12.5% of simple fractures had associated trauma APR-DRGs. Conclusion: APR-DRGs appeared to only capture a fraction of the entire trauma population and it tends to be the more severely ill patients. As a result, the administrative data was not able to accurately answer hospital or operating room utilization as well as specific information on diagnosis categories regarding trauma patients. APR-DRG administrative data should not be used as the only data source for evaluating the needs of a trauma program.